Diplomacy, communication, and peace : selected essays - Maley, William, 1957-; Routledge (Firm) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book is composed of interconnected essays which reflect on challenging new issues related to diplomacy, communication, and peace. This book begins by drawing out some of the challenges for diplomacy that arise from modern theories of semantics and of strategic communication, as well as those posed by the need for secrecy, and by the activities of agents of influence. It then proceeds to examine important issues in contemporary diplomacy, including refugee diplomacy, humanitarian diplomacy, sovereignty, norms and consular activities. It concludes with an exploration of dilemmas that confront attempts to promote peace through multilateral means, such as the limitations of peacemaking diplomacy, the difficulty of promoting democratic governance, and the problems associated with dealing with morally repugnant actors. The book is grounded in the conception of diplomacy as a social practice with multiple players, and recognises that 'the state' has many different elements, and that 'state actors' live in worlds shaped not just by their relations with other states, but also by their own complex domestic politics. This book will be of much interest to students of diplomacy, foreign policy and International Relations"--
Introduction: Diplomacy, diplomatic studies, and diplomatic history -- Minimal English and diplomacy -- Terrorism, diplomacy and strategic communication -- Secret and quiet diplomacy -- Agents of influence -- Refugee diplomacy -- Australia's refugee policy : domestic politics and diplomatic consequences -- The United Nations, NGOs and the land-mines initiative : an Australian perspective -- Humanitarianism and humanitarian diplomacy -- Trust, legitimacy, and the sharing of sovereignty -- Norms as frames for institutions -- Risk, populism and the evolution of consular responsibilities -- Peacekeeping and peacemaking -- Democratic governance and post-conflict transitions -- The United Nations and ethnic conflict management : lessons from the disintegration of Yugoslavia -- Negotiating with morally-repugnant actors.
OCLC-licensed vendor bibliographic record.
Keywords: Diplomacy; International relations; Peace-building.; Communication in politics; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / Peace